Leveraging Fluorescent Emission to Unitary Yield: Dimerization of Polycyclic Aromatic Hydrocarbons. Issue 3 (28th February 2019) - Miletić, Tanja; Biot, Nicolas; Demitri, Nicola; Brancato, Giuseppe; Kariuki, Benson M.; Bonifazi, Davide
Abstract: We report on the synthesis and characterization of novel substituted 1, 1′‐biperylene‐2, 2′‐diols in which the dihedral angle between the two polycyclic aromatic hydrocarbon (PAH) units is tailored from ca . 60° to ca . 90° in the solid state by introduction of cyclo‐etheric straps or sterically hindered groups such as the triisopropylsilyl (TIPS) group. Depending on the type of substitution, we lock the dihedral angle between the perylenyl moieties enabling fine‐tuning of the molecular optoelectronic properties, with the molecules displaying the smallest angles acting as exceptionally strong emitters with unitary quantum yields. Abstract :